LEGAL ANALYSIS OF CHILD PROTECTION AGAINST CHILDREN AS PERPETRATORS OF SEXUAL VIOLENCE CRIMES IN INDONESIA - Izdihar, Naufal; Guntara, Deny; Abas, Muhamad (Jurnal Ilmiah Advokasi, 2025)
As the times advance, cases of children as casualties of sexual viciousness are expanding day by day and very some children are included as culprits of sexual viciousness carried out like grown-ups, this has ended up a unused questioning that stresses numerous parties. This investigate points to discover out how the Child Security Law and the Adolescent Criminal Equity Framework are directed in cases of children as culprits of sexual viciousness and what components can trigger children to commit criminal acts of sexual savagery. This inquire about employments a sort of standardizing juridical inquire about strategy utilizing a few approaches, namely the statutory approach, the case approach additionally employing a comparative approach. The discoveries in this inquire about appear that the control of children as culprits of sexual savagery has not been completely controlled in statutory directions and there's a require for a survey of the age limits for children both within the Child Assurance Law and the Juvenile Criminal Equity Framework, seeing that there's a move in children's mentality at this time. . There are variables that impact children to gotten to be culprits of sexual savagery, specifically need of parental supervision, the impact of globalization, negligible devout instruction and natural variables. The conclusion in this case is that preoccupation can be endeavored in the event that the greatest criminal term is 7 a long time, but in cases of sexual viciousness it cannot be carried out, at that point detainment will be forced as a final resort.Keywords : Children; Sexual Violence; Legal Protection; Criminal Acts.